Factors influencing changes in the quality of life of the Hainan migratory population with hypertension: a survey of the Chengmai mangrove bay community - Qiaochun Chen; Jing Zhou; Na Li; Luming Liu; Yixuan Li; Wenfang Long; Ziyue Luo; Yunru Liu; Sha Xiao (BMC Public Health)
Abstract Background Hainan is a tropical island in China with a large migratory population. Study have reported that the blood pressure of Hainan elderly hypertensive migratory population decreased significantly, which may be related to the improvement of environment and quality of life (QoL). Understanding the changes of QoL of these people before and after coming to Hainan and its influencing factors can provide a basis for the prevention and control of hypertension. Methods A cross-sectional study of elderly hypertensive migratory population were conducted in Chengmai Mangrove Bay community of Hainan from December 2021 to January 2022. Convenience sampling was used to recruit elderly hypertensive migratory individuals reside stay of longer than one month. After obtaining informed consent, we investigated the demographic characteristics of the participants and evaluated their QoL with the SF-36 twice; one round of the SF-36 was about their hometown, and the other round was about living in Hainan for 1 month. The Cronbach’s α coefficient and KMO value of SF-36 were both greater than 0.8, indicating good reliability and validity. The difference in blood pressure between that observed in Hainan and that observed in their hometowns was used to determine whether the Body Pain change in the subjects decreased or did not decrease after migrating to Hainan. Univariate analysis was performed via paired t tests and Kendall’s tau-b tests, and multiple linear regression analysis and logistic regression analysis were used to analyse the factors influencing the QoL of the participants. Results A total of 305 hypertensive migratory individuals participated in this study. Among them, there were 148 males (48.52%) and 157 females (51.48%), with a mean age of 68.61 ± 9.39 years. The postmigration scores for the 8 subscales of QoL, the global score, the Physical Component Score, and the Mental Component Score were all higher than the scores for their hometowns (P < 0.05). Factors such as gender (r = 0.139, P < 0.05), age (r = 0.209, P < 0.05), and level of education (r=-0.133, P < 0.05) were associated with changes in the QoL of the participants. The conditions of green and water spaces in their hometown, sleep habits in their hometown and ventilation habits in their hometown were the major factors influencing the subjects’ QoL in their hometown (P < 0.05). The factors that influenced the improvement in the subjects’ QoL in Hainan included hypertension classification (OR = 2.336, 95% CI: 1.125 ∼ 4.853, P = 0.023) and BMI (OR = 6.402, 95% CI: 1.009 ∼ 40.624, P = 0.049). Conclusion The QoL of hypertensive migratory population in Hainan improved with respect to individual health, physiological function, psychological function and social function. The lower the hypertension classification and BMI are, the greater the improvement in the QoL of hypertensive migratory population.